Impact of a Brief Family Skills Training Programme (“Strong Families”) on Parenting Skills, Child Psychosocial Functioning, and Resilience in Iran: A Multisite Controlled Trial - Karin Haar (MDPI AG, 2021)
Caregivers have a key role in protecting children’s wellbeing, and, with appropriate skills, can prevent a multitude of negative social outcomes, particularly in challenged or humanitarian settings. Accordingly, the Strong Families programme was designed as a light touch family skills programme, with a focus of supporting caregiving during stressful situations. To evaluate the short-term impact of the Strong Families programme, we performed a time-convenience, randomized, controlled trial in Iran. A total of 292 families (63% from Iranian decent, 39% from Afghan decent, and 1% other), with children aged eight to twelve years, were recruited through ten centers in Iran and allocated to an intervention (n = 199) or waitlist/control group (n = 93). The two groups did not differ demographically at baseline. We assessed families prospectively, through three scales, PAFAS (parenting and family adjustment scales), SDQ (strengths and difficulties questionnaire), and CYRM-R (child and youth resilience measure). Caregivers in the intervention group improved (highly) statistically significantly on all but one PAFAS subscales (parental consistency, coercive parenting, positive encouragement, parental adjustment, family relationships, and parental teamwork), which was not noted in the waitlist group. On the SDQ, there were (highly) significant positive changes in scores in the intervention group on all sub-scales and the “total difficulty scale“, whereas the waitlist/control group also improved on three (prosocial, conduct problems, and hyperactivity) of the five SDQ subscales. Children originating from Afghanistan improved significantly on the overall resilience scale of the CYRM-R in the intervention group, but not in the waitlist/control group. Overall, all our stratified results of the different scales reflect an accentuated improvement in families with higher levels of problems at baseline. Our comparative results indicated a strong alignment of the strong families programme with its intended short-term impact, per its logical frame on parenting practices and family management skills, children behaviour, caregivers and children mental health, and capacity to cope with stress. We postulate that the potential nudging or diffusion of knowledge (cross-contamination between intervention and waitlist/control group) at the community level could explain improvements in the waitlist/control group on some indicators, however, further research on this is recommend.